Gender Disparities in Oncology: A Report From Four Countries in Latin America - Julia Ismael; Paola Montenegro; Bettina Müller; Regina Barragan-Carrillo; Jazmín Hernández-Marín; Edith A. Fernández-Figueroa; Jesús Argueta-Donohué; Erika Ruiz-Garcia (JCO Global Oncology)
PURPOSEWomen represent a growing force in oncology but remain underrepresented in high-level positions. Gender-related challenges affect academic progression, research, and clinical practice. This manuscript aims to describes gender-based professional development challenges faced by women in oncology in Latin America (LATAM).MATERIALS AND METHODSWe conducted a multicenter, cross-sectional study among LATAM oncologists using a 27-item questionnaire on the basis of the European Society for Medical Oncology Women for Oncology Survey. Our analysis focused on male-female disparities, excluding other gender identities. Logistic regression models were used to calculated odds ratios (ORs) for gender inequity, wage disparity, workplace and sexual harassment, and family development. Statistical analyses were performed using SPSS version 26, with the significance set at P < .05.RESULTSWe analyzed 254 participants from Argentina, Chile, Mexico, and Peru, mostly females (88%) and based in Mexico (55%). Most were attending physicians (68%), 51.5% worked 41-60 hours, and 33.4% reported gender equity initiatives. Gender inequity was significantly higher among women (83%) than among men (37%), with the female gender identified as a risk factor (OR, 15.67; P < .001). Workplace harassment was reported by 60% of women and 19% of men, whereas sexual harassment was experienced by 34% of women and 16% of men (OR, 2.78; P < .05). Sixty-five percent reported that men had the highest salaries. Logistic regression indicated that working 20-40 hours per week was associated with the likelihood of women having children (OR, 3.0; P < .01), as was working 41-60 hours (OR, 1.97; P < .01). However, holding an attending or resident position was associated with significantly lower childbearing ratesCONCLUSIONOur findings indicate that Women oncologists in LATAM report experiencing higher rates of gender-based inequity and harassment and remain underrepresented in leadership and high-earning roles.